2009
DOI: 10.4162/nrp.2009.3.2.84
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of inflammatory molecule expression on 3T3-L1 adipocytes by berberine is not mediated by leptin signaling

Abstract: In our previous study, we have shown that berberine has both anti-adipogenic and anti-inflammatory effects on 3T3-L1 adipocytes, and the anti-adipogenic effect is due to the down-regulation of adipogenic enzymes and transcription factors. Here we focused more on anti-inflammatory effect of berberine using real time RT-PCR and found it changes expressions of adipokines. We hypothesized that anti-adipogenicity of berberine mediates anti-inflammtory effect and explored leptin as a candidate mediator of this signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
4
12
0
Order By: Relevance
“…Recently, it have shown that berberine has no effect on leptininduced STAT-3 phosphorylation [Choi et al, 2009]. Here we found that berberine also antagonizes LPS-induced IkBa activation and IFN-g-induced STAT-1 and STAT-3 phosphorylation (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Recently, it have shown that berberine has no effect on leptininduced STAT-3 phosphorylation [Choi et al, 2009]. Here we found that berberine also antagonizes LPS-induced IkBa activation and IFN-g-induced STAT-1 and STAT-3 phosphorylation (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, the inhibition of MAP kinase involved in berberine treatment might be dependent on cell types and experimental condition. Notably, numerous reports have also shown that berberine suppresses IL-1b and TNF-a production via the inhibition of NF-kB signaling pathway [Hsiang et al, 2005;Lee et al, 2007; Ho et al, 2009].Recently, it have shown that berberine has no effect on leptininduced STAT-3 phosphorylation [Choi et al, 2009]. Here we found that berberine also antagonizes LPS-induced IkBa activation and IFN-g-induced STAT-1 and STAT-3 phosphorylation (Fig.…”
supporting
confidence: 66%
“…BR extract showed more than 75% of viability of cells during in-vitro study. The extract of BR revealed significant inhibition in differentiated cell as compared to non-differentiated cell in 3T3-L1 cell line [31]. Improvement in lipid profile reduces the possibilities of diabetes induced obesity and cardiovascular diseases [32].…”
Section: Discussionmentioning
confidence: 99%
“…The association between fasting glucose and log-transformed 25OHD concentration was of borderline significance after accounting for ethnicity, age and body mass index in multivariate analyses. The odds ratio of gestational diabetes in women with 25OHD < 50 nmol/L did not reach statistical significance (1.92, 95% confidence interval 0.89-4.17) (Clifton-Bligh et al, 2008). In another study total prevalence of vitamin D deficiency (<25 nmol/L) was 70.6% in pregnant women.…”
Section: Vitamin D Deficiency and Gestational Diabetesmentioning
confidence: 98%
“…Supplementation by varying forms of adiponectin improved control of insulin, blood glucose and triglyceride levels in mouse models. Berbelin, a herbal folk medicine, has been shown to increase adiponectin expression which partly explains its advantageous effects on metabolic disturbances (Choi et al, 2009). A reduction in adiponectin expression is associated with insulin resistance in animal models.…”
Section: Adiponectin 211 Adiponectin Structurementioning
confidence: 99%